A workflow for large‐scale empirical identification of cell wall N‐linked glycoproteins of tomato (Solanum lycopersicum) fruit by tandem mass spectrometry. Issue 16 (14th August 2013) - Thannhauser, Theodore W.; Shen, Miaoqing; Sherwood, Robert; Howe, Kevin; Fish, Tara; Yang, Yong; Chen, Wei; Zhang, Sheng; Guttman, Andras
<x xml:space="preserve">Abstract</x> Glycosylation is a common PTM of plant proteins that impacts a large number of important biological processes. Nevertheless, the impacts of differential site occupancy and the nature of specific glycoforms are obscure. Historically, characterization of glycoproteins has been difficult due to the distinct physicochemical properties of the peptidyl and glycan moieties, the variable and dynamic nature of the glycosylation process, their heterogeneous nature, and the low relative abundance of each glycoform. In this study, we explore a new pipeline developed for large‐scale empirical identification of N‐linked glycoproteins of tomato fruit as part of our ongoing efforts to characterize the tomato secretome. The workflow presented involves a combination of lectin affinity, tryptic digestion, ion‐pairing HILIC, and precursor ion‐driven data‐dependent MS/MS analysis with a script to facilitate the identification and characterization of occupied N‐linked glycosylation sites. A total of 212 glycoproteins were identified in this study, in which 26 glycopeptides from 24 glycoproteins were successfully characterized in just one HILIC fraction. Further precursor ion discovery‐based MS/MS and deglycosylation followed by high accuracy and resolution MS analysis were used to confirm the glycosylation sites and determine site occupancy rates. The workflow reported is robust and capable of producing large amounts of empirical data involving N‐linked glycosylation sites and their associated glycoforms.